EMPOWERING WOMEN: HOW SHOULD THE OMANI STATE CONTINUE SUPPORTING WOMEN WORKING IN ITS HANDICRAFTS INDUSTRIES? - Hansrod, Humaira (PEOPLE: International Journal of Social Sciences, 2019)
Improving the economic status of women around the world has positive effects on social, economic, and political development. One inequality that women in the MENA have and continue to face is economic inequality, manifested mainly through various barriers from participating in the formal labor force and discrimination at work and public spaces. Women’s empowerment is a frequently cited goal of most countries’ development policies and key to addressing gender inequalities. The field research sought to contextualize women’s empowerment in the handicrafts sector in Oman by soliciting the participants’ reactions on factors that are often used to measure empowerment through work. The paper assesses potential pathways that position employment, and the development of entrepreneurial know-how, within an empowerment approach. Using a qualitative approach, it applies the sustainable livelihood framework to identify several constraints to women’s work and provides a micro-level perspective of Oman’s handicrafts sector.